Tamanho e forma do Centauro (2060) Chiron e a busca por estruturas em seu entorno a partir de ocultações estelares - Pereira, Chrystian Luciano (2020)
Centaurs are minor bodies in the Solar System that orbit the Sun between Jupiter and Neptune’s orbits. The first Centaur discovered was (2060) Chiron, when it received the provisional designation of 1977 UB. Like other Centaurs discovered later, Chiron exhibited cometary activity and coma in observations in the years 1988 and 1989, which also earned it the designation of a comet (95/P Chiron). In stellar occultations in the ’90s, structures in the inner coma were interpreted as collimated jets of material expelled by the nucleus. Symmetric structures around the center of (2060) Chiron were also observed in an occultation in 2011, raising the hypothesis that a ring system may surround the object. This work contains the investigation about the size, shape and the search for structures around the Centaur (2060) Chiron in the light curves of two stellar occultations in the last two years. On November 28, 2018, (2060) Chiron occulted a G ∼ 17.2 magnitude star. Data was successfully acquired at the South African Astronomical Observatory (SAAO) with the detection of the object’s nucleus. With a 31.3±0.2 seconds duration, the chord size is estimated at 179.8±1.4 km. In the stellar occultation on September 8, 2019, (2060) Chiron occulted a star with magnitude R ∼ 16.5. The observations were made in five sites in Europe; two positive ones in Belgium, two positive ones in France and one telescope in Spain obtained a negative chord close to the body’s shadow. As all telescopes were medium-sized, the data showed a low signal-to-noise ratio, só it was impossible to search for secondary events in the light curves of the 2019 event. Despite this, this multi-chord occultation allowed to constrains the size and shape of the object. In this work, in addition to presenting, for the first time, restrictions to the size and shape of Chiron, we use the data obtained in the 2018 occultation to perform a search for the proposed rings, determining limits for the detection of any material or other structure in the equatorial plane, or radially diffuse, orbiting (2060) Chiron.